2018
DOI: 10.1038/s41467-018-02969-8
|View full text |Cite
|
Sign up to set email alerts
|

3D microfluidic liver cultures as a physiological preclinical tool for hepatitis B virus infection

Abstract: With more than 240 million people infected, hepatitis B virus (HBV) is a major health concern. The inability to mimic the complexity of the liver using cell lines and regular primary human hepatocyte (PHH) cultures pose significant limitations for studying host/pathogen interactions. Here, we describe a 3D microfluidic PHH system permissive to HBV infection, which can be maintained for at least 40 days. This system enables the recapitulation of all steps of the HBV life cycle, including the replication of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
185
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(187 citation statements)
references
References 55 publications
2
185
0
Order By: Relevance
“…20 Another group applied the self-assembling (SACC) PHH culture system for HBV persistence infection and preclinical studies. PHH is the best cell model for HBV studies.…”
Section: Discussionmentioning
confidence: 99%
“…20 Another group applied the self-assembling (SACC) PHH culture system for HBV persistence infection and preclinical studies. PHH is the best cell model for HBV studies.…”
Section: Discussionmentioning
confidence: 99%
“…Cells in this model remain viable and functional for at least seven days, as judged by calcein acetoxymethyl (AM) and albumin staining, respectively. The model has been used for a variety of applications, including pharmacokinetic studies, evaluation of hepatotoxicity, modeling of nonalcoholic fatty liver disease (NAFLD), and hepatitis B viral infections . In addition, a multitude of small companies and start‐ups provide liver‐on‐a‐chip platforms for which at present very limited peer‐reviewed benchmarking data are available.…”
Section: D Culture Paradigms For Phhmentioning
confidence: 99%
“…B) PHH cultured as liver‐on‐chip are susceptible to hepatitis B virus (HBV) infections as judged by immunofluorescence of HBV viral antigens (HBsAg and HBcAg) ten days after infection. Reproduced with permission . Copyright 2018, Nature Publishing Group.…”
Section: Applications Of Advanced Primary Human Hepatocyte Culture Momentioning
confidence: 99%
See 1 more Smart Citation
“…The findings in liver tissues of chimpanzees and CHB patients as well as experiments in vitro have shown that the endogenous IFNα and interferon‐stimulated genes (ISGs) were all not induced while HBV infection . Some research reported that the level of IFNα released by HBV‐infected PHH cells was even decreased and the expression of antiviral genes was hardly observed even in co‐culture with Kupffer cells (KC) …”
Section: Relationship Between Host and Hbvmentioning
confidence: 99%